Impact of prophylactic cytomegalovirus immunoglobulin on cytomegalovirus viremia and graft function in ABO-incompatible living donor kidney transplantation: a retrospective analysis - Zhong, Linhong; Tang, Shijie; Pu, Zhongping; Chen, Kai; Di, Wenjia; Hou, Yifu; Yang, Hongji (Frontiers in Immunology, 2025)
BackgroundCytomegalovirus (CMV) infection poses a significant risk to kidney transplant recipients. CMV immunoglobulin shows promising prophylactic effect, particularly in the context of ABO-incompatible transplants. However, its efficacy in preventing CMV viremia remains underexplored.MethodsIn this retrospective study, we enrolled patients who underwent ABO-incompatible living donor kidney transplantation between May 2021 and September 2023. Prophylactic CMV immunoglobulin was administered at 100 mg/kg weekly for one month in the combined prophylaxis group, while no prophylactic medication was applied in the preemptive therapy group. The primary outcome was measured as the incidence of clinically relevant CMV viremia (CMV DNA >10,000 copies/mL) within one year after transplantation. Both groups received standard preemptive therapy with ganciclovir or valganciclovir after diagnosed with clinically relevant CMV viremia.ResultsProphylactic CMV immunoglobulin significantly reduced clinically relevant viremia incidence compared to preemptive therapy group (16.0% vs. 34.0%, P = 0.04). At the end of the follow-up, the combined prophylaxis group showed higher eGFR (56.40 ± 14.19 vs. 47.30 ± 13.01 mL/min/1.73m², P = 0.0014) and lower serum creatinine (146.5 ± 57.07 vs. 171.2 ± 51.48 µmol/L, P = 0.0274). However, no significant differences in renal function were observed between the groups at1,3, or 6 months post-transplantation.ConclusionCMV immunoglobulin represents a promising prophylactic option for reducing clinically relevant CMV viremia incidence and delaying infection onset in ABO-incompatible kidney transplant recipients.